Methodological Approaches for Assessing the Link between Supply Chain and Organizational Culture - Nadezda D. Guskova; Aleksandra V. Erastova; Irina N. Krakovskaya (International Journal of Supply Chain Management, 2020)
Abstract— The aim of this paper is to expand the knowledge of buyer-supplier relationships by investigating the extent to which organisational cultural fit between a buyer and supply chain participants influences performance. Findings demonstrate that complementarity rather than congruence between the supply chain partners achieved successful performance outcomes. Organisations in the high-performing supply chain had significantly different cultural profiles, reporting significant statistical differences across all six cultural dimensions. Organisations in the low-performing supply chain had almost identical profiles across all six cultural dimensions with significantly lower mean scores across each dimension. This article presents methodological approaches for assessing the organizational culture development of an educational institution. The research purpose is to study the feasibility and advisability of applying various methods to assess the level of the organizational culture development on supply chain management. The authors conducted an empirical study using quantitative methods (the maturity matrix of sustainable development of the organization and the Denison model), adapted to evaluate the level of the organizational culture development in a supply chain management.